Setup Reduction Integration Model and Lot Size Determination in Export Coffee Processing Production Systems - Sahat Dapottua Sitompul (PT Inovasi Pratama Internasional, 2022)
In the last 10 years, competition between companies (business entities) has become increasingly sharp. The company continuously strives to reduce production costs and improve the quality of its products. The development of cooperation with suppliers is one of the efforts made by many companies to achieve this goal. Currently no single company can manufacture its products without the involvement of suppliers. Collaboration in determining policies for supplying and manufacturing companies in terms of supply creates a production system network ( PSN) that has a collaborative relationship pattern . This relationship creates an innovation in the manufacturing system which certainly brings benefits to both parties. Silver, Pyke and Peterson (1998) suggested the need for coordination in determining inventory policies between suppliers and manufacturers, with the aim of being able to make savings on the aspects of setup costs per unit, ordering costs per unit and transportation costs per unit. Determination of inventory policy as a result of cooperation between suppliers and manufacturers creates the need to determine the combined lot size. The research objective is to obtain a combined lot size determination model that takes into account the aspects of reducing setup and improving production quality. The results of demand forecasting in the future are the basis for calculations in production planning, inventory control and calculating the cost of procuring the most economical raw materials.